Psychology of Decision Making in Crisis Management - Arva Syadiva; Kinanti Dhea (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study investigates psychological factors influencing decision-making in crisis management, a crucial area given the frequent observation of suboptimal decisions in real-life crises. We hypothesize that cognitive biases and negative emotions significantly impair decision quality. Using a structured online questionnaire, data were collected from 10 crisis management professionals. The findings, while exploratory due to the small sample size, indicate a negative trend: higher levels of cognitive biases and negative emotions tend to correlate with lower decision quality. Statistical significance could not be established. Despite these limitations, this study highlights the important role of psychological aspects in crisis decision-making, emphasizing the need for further research with larger samples to inform more effective crisis preparation.